Billingual phenomenon usage in presenting make up tutorial - Hanny Akbari; Arif Hidayat; Sayyid Khairunnas (LADU: Journal of Languages and Education, 2020)
Background: The writer interested to analyze the code switching and code mixing in Suhay Salim’s video because she is a bilingual speaker. She is able to speak both Bahasa and English. In each her video, Suhay Salim always uses code switching and code mixing. Purpose: The objective of this research is to know the types of code switching and code mixing used in the video, and also to know the reasons why the speaker used code switching and code mixing in her YouTube video. Design and methods: The data were collected through library research. The method of this research is descriptive qualitative method. Results: The result of this analysis is indicated that: (1) Types of code switching that found are situational code switching and metaphorical code switching. (2) types of code mixing found are insertion and alternation. (3) while the reasons to use code switching and code mixing are talking about particular topic, real lexical need, interjection, repetition used for clarification, and expressing group identity.